A Population-based Analysis of French Transfusion Practice for Women Experiencing Severe Postpartum Hemorrhage. Issue 1 (24th March 2021) - Deleu, F.; Deneux-Tharaux, C.; Chiesa-Dubruille, C.; Seco, A.; Bonneta, M.P.
Abstract : ( Int J Obstet Anesth . 2020;42:11–19) Severe postpartum hemorrhage (SPPH) is the leading cause of severe maternal mortality worldwide. Blood transfusion is a central part of managing SPPH, but there is a lack of prospective population-based studies on transfusion practices. The EPIMOMS study on severe acute maternal morbidity provides data on transfusion management for SPPH. This retrospective study used data from the EPIMOMS study and aimed to describe transfusion practices and evaluate those practices in terms of compliance with French PPH management guidelines.